Estimation of Enrofloxacin Residues in Broilers Tissues Before and After Heat Treatments (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The research had been conducted to the resid assess the use of Enrofloxacin in broiler tissues before and after heat treatments. A total number of 60, on day-old broiler chicks, were given Enrofloxacin (10%) at a dose of 1ml /2 letter of drinking water at 38-40 days old. Birds had been euthanized at 41,43 and 45 days. assessment of Enrofloxacin residue was estimated in their muscles and livers before and after heat treatments. Results illustrated a significant difference of Enrofloxacin residues in pectoral muscles at 41,43 and 45 days before heat treatment and it was non-significant after heat treatment in the same days. Moreover, there were high Significant differences (P